Pengaruh Gaya Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan PT Mega Telekom di Kota Batam - Mauli Siagian; - defrianti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
The increasingly competitive level of business today, requires every company to have the advantage to succeed in competing. The success of each company is inseparable from the human resources factor. Good and high quality human resources will improve employee performance. The purpose of this study is to determine the effect of leadership style and compensation on employee performance at PT Mega Telekom in Batam. The sampling technique used in this study is saturated sampling, with data collection methods through questionnaires. The sample used in this study were 150 respondents who make all employees of PT Mega Telekom as respondents. Furthermore, data that have been collected in this study were analyzed with multiple linear regression analysis and processed using SPSS (Statistic Product and Service Solution) version 24. The results in this study indicate that the t test, known that for independent variables of leadership style has significant effect on employee performance and compensation significantly affect employee performance. F test results indicate the leadership style variable and compensation variable together affect the employee perfomance.